1999
DOI: 10.1007/s005200050268
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of siblings to childhood cancer: a literature review

Abstract: Studies concerning sibling adjustment to childhood cancer and published since 1980 were reviewed. Sibling distress was described in terms of emotional, socio-behavioral, academic, physical and positive reactions. Secondly, characteristics and coping resources of siblings that are related to adjustment were summarized. Thirdly, the families' functioning, parental coping resources and family events that relate to adjustment were described. Finally, relevant aspects of the illness that may influence adjustment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 42 publications
5
93
0
10
Order By: Relevance
“…Statistical significance was defined as p < 0.05 for acceptance in the enter model. were between 19 and 23 years (mean = 24.0, SD = 3.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] at the time of investigation. The average time since loss was 6.3 years (range 2-9, SD = 2.3).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was defined as p < 0.05 for acceptance in the enter model. were between 19 and 23 years (mean = 24.0, SD = 3.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] at the time of investigation. The average time since loss was 6.3 years (range 2-9, SD = 2.3).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified maladaptive levels of anxiety and depression in healthy siblings of childhood cancer patients [Cain et al, 1964;Spinetta, 1981], although the distress tends to remit once the cancer treatment stops [Van Dongen-Melman et al, 1995]. One possible explanation is that overwhelmed parents may neglect the psychological and physical needs of their healthy children [Sahler et al, 1994;Zeltzer et al, 1996;Houtzager et al, 1999;Murray, 2000] and, perhaps, leave them to contend with feelings of loneliness, fear, anger, hate and jealousy [Martinson et al, 1990;Murray, 1998]. In this way, parent-child bonding or attachment may be harmed and lead to psychological distress in the child [Fanos, 1997;Murray, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…These behaviors contribute to the burnout care providers experience, 11,12 but also leave a sad and bitter memory of this period in the family, which is even more intense if the child dies. However, the feeling of their value is based on being competent as parents (for all their children [13][14][15] ), but it is also based on preserving their family and social role. Finally, we should not forget that such units are 'a closed world', where the parents spend days and weeks together, and exert both a positive and a negative influence on each other.…”
Section: Discussionmentioning
confidence: 99%